Harmonizing Duties of Board Members in the Anthropocene: When Expectations Meet Reality - Weber, Anne-Marie; Mittwoch, Anne-Christin (Review of European and Comparative Law, 2023)
The article confronts the European Commission’s climate policy-seconded endeavors regarding board members’ duties which it has expressed in its proposal for a Corporate Sustainability Due Diligence Directive (CSDDD Proposal) published in February 2022 with a comparative analysis of the current legal state of play in Germany and Poland. We claim that the Commission has neglected to adequately address the current understanding of board members’ duties across the Member States, which has ultimately led to the deletion of the Proposals’ provisions’ referring to the board members’ duty of care in the legislative work conducted within the Council of the European Union in November 2022. There is a possibility that these provisions (Art. 25 and 26 CSDDD Proposal) will be reinserted during the trialogue, but this is unlikely at this point. Notably, the Commission’s declaration on a mere clarifying role of the proposed harmonization measure regarding board members’ duties seems imprecise and prompts a weak interpretation of the proposed provisions, which contradicts the proclaimed policy goals. Germany might serve as an example of a Member State in which implementing the Commission’s understanding of the board members’ duty of care would not have significantly modified national company law, regardless of the interpretation chosen for the depth of the provision. If, however, a strong or medium mode of interpretation was applicable, Poland would actually be obliged to amend its legal framework fundamentally. Therefore, we contend that the legislative work on the discussed proposal was tainted by the flawed presumption that the proposed harmonization measure would merely summarize existing rules for board members’ duties. Based on the observations from our emblematic comparative juxtaposition, we argue that the idiosyncratic concepts of board members’ duties across Member States have not been sufficiently recognized as a harmonization challenge by the Commission. We contend that these methodological deficiencies led to an inconclusive wording of Article 25 of the Commission’s proposal and ultimately created an insurmountable barrier to political agreement within the Council and the “fall” of the complete concept of setting a standard of due care for board members in the proposed directive. Consequently, we claim that when jostling such a controversial and deep harmonization measure, the Commission must play its legislative A-game to have a shot at approval by the Council and later effective implementation by the Member States.